Kajian Hukum terhadap Status Jaminan Kebendaan Milik Pihak Ketiga dalam Kepailitan Berdasarkan Undang-Undang No. 37 Tahun 2004 Tentang Kepailitan & Penundaan Kewajiban Pembayaran Utang - Daniel Baja; Heri Qomarudin (Decisio: Jurnal Ilmiah Hukum, 2026)
This study analyzes the legal status of third-party property used as collateral for the debts of bankrupt debtors under Law No. 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations. It examines whether third-party property can be classified as part of the bankruptcy estate and how creditors holding such collateral are affected by the law. Using a normative legal approach, this research reviews relevant legislation and court decisions. The findings show that third-party property pledged as collateral is not automatically considered bankruptcy assets. However, if the collateral is inseparable from the debtor's assets, it may be treated as part of the bankruptcy estate. Additionally, the study explores the obligations of secured creditors to comply with the Bankruptcy Law in claiming their rights to collateral. Despite being entitled to collateral, creditors must follow legal procedures to safeguard the interests of all parties involved in the bankruptcy process. This study offers insights into the legal implications of collateral on third-party assets and its impact on creditors' rights in Indonesia's bankruptcy proceedings.